Management of Local Content Collections as an Effort to Preserve Regional Culture at Public Library - Adri Seprian Saputra; Aang Gunaidi; Fransiska Timoria Samosir (Record and Library Journal, 2023)
Background of the study: Local Content is an important collection owned by the   library as a source of information about local entities for users. Purpose: This study aims to find out how collection management is carried out by the Library and Archives Service of Bengkulu Province on local content collections and what efforts have been made toward cultural preservation, especially on local content collections. Method: This type of research is qualitative with a descriptive approach. Data collection techniques in this study used observation and interview technique. Findings: Based on data sourced from interviews with deposit service librarians, namely the Library and Archives Service of Bengkulu Province, they have managed local content collection well in procurement, processing, and storage. However, there needs to be an evaluation to develop the procurement of local content collections due to the relatively long flow of collection procurement. Conclusion: The Library and Archives of Bengkulu Province has carried out activities in order to maintain the preservation of collections and in managing deposit collections including, collecting, managing, and preserving.